Standards of specialized diabetes care. Edited by Dedov I.I., Shestakova M.V. (7th edition) - Ivan Ivanovich Dedov; Marina Vladimirovna Shestakova; Gagik Radikovich Galstyan; Olga Rafael'evna Grigoryan; Rosa Michailovna Esayan; Victor Yur'evich Kalashnikov; Tamara Leonidovna Kuraeva; Dmitriy Valentinovich Lipatov; Alexander Yur'evich Mayorov; Valentina Alexandrovna Peterkova; Olga Michailovna Smirnova; Elena Georgievna Starostina; et al. (Сахарный диабет)
We are glad to present the 7th Edition of Standards of Diabetes Care.These evidence-based guidelines were designed to standardize and facilitate diabetes care in all regions of the Russian Federation.The Standards are updated on the regular basis to incorporate new data and relevant recommendations from national and international clinical societies, including World Health Organization Guidelines (WHO, 2011, 2013), International Diabetes Federation (IDF, 2011, 2012, 2013), American Diabetes Association (ADA, 2012, 2015), American Association of Clinical Endocrinologists (AACE, 2013), International Society for Pediatric and Adolescent Diabetes (ISPAD, 2014) and Russian Association of Endocrinologists (RAE, 2011, 2012).Current edition of the ?Standards? also integrates results of completed randomized clinical trials (ADVANCE, ACCORD, VADT, UKPDS, etc.), as well as findings from the national studies of diabetes mellitus (DM), conducted in close partnership with a number of Russian hospitals.Latest data indicates that prevalence of DM increased during the last decade more than two-fold, reaching some 387 million patients by the end of 2014. According to the current estimation by the International Diabetes Federation, 592 million patients will be suffering from DM by 2035. These observations resulted in the UN Resolution 61/225 passed on 20.12.2006 that encouraged all Member States "to develop national policies for the prevention, treatment and care of diabetes".Like many other countries, Russian Federation experiences a sharp rise in the prevalence of DM. According to Russian State Diabetes Register, there are at least 4.1 million patients with DM in this country. However, the epidemiological survey conducted by the Federal Endocrinology Research Centre during 2002-2010 suggests that actual prevalence is 3 to 4 times greater than the officially recognized and, by this estimate, amounts to 9-10 million persons, comprising 7% of the national population.Severe consequences of the global pandemics of DM include its vascular complications: nephropathy, retinopathy, coronary, cerebral and peripheral vascular disease. These conditions are responsible for the majority of cases of diabetes-related disability and death.Current edition of the "Standards" emphasizes the patient-oriented approach in making decisions on therapeutic goals, such as levels of glycaemia and blood pressure. It also features updated guidelines on the management of vascular complications.This text represents a consensus by the absolute majority of national experts, achieved through a number of fruitful discussions held at national meetings and forums. These guidelines are intended for endocrinologists and diabetologists, primary care physicians, cardiologists and other medical professionals involved in prevention and treatment of diabetes mellitus.